If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -98 = -3x + -4(-4x + 5) Reorder the terms: -98 = -3x + -4(5 + -4x) -98 = -3x + (5 * -4 + -4x * -4) -98 = -3x + (-20 + 16x) Reorder the terms: -98 = -20 + -3x + 16x Combine like terms: -3x + 16x = 13x -98 = -20 + 13x Solving -98 = -20 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -98 + -13x = -20 + 13x + -13x Combine like terms: 13x + -13x = 0 -98 + -13x = -20 + 0 -98 + -13x = -20 Add '98' to each side of the equation. -98 + 98 + -13x = -20 + 98 Combine like terms: -98 + 98 = 0 0 + -13x = -20 + 98 -13x = -20 + 98 Combine like terms: -20 + 98 = 78 -13x = 78 Divide each side by '-13'. x = -6 Simplifying x = -6
| 1+t=-1 | | -2d=-24 | | w+2=4 | | k-5=-16 | | 5d=10 | | -7+w=-16 | | 4x^2+5xy-6y^2+5x^2+3y^2-2y= | | -1=x-1 | | t-4=-4 | | -2=n+2 | | -1+x=-11 | | 7a=-42 | | -4x-5(2x-10)=190 | | 2y-13=-6x-5 | | 0=b+4 | | 13=d+3 | | 1=a-10 | | -1+w=3 | | k+5=-4 | | -6-7x=-118 | | -8+b=-11 | | -8+d=-14 | | 3=k-4 | | -3=k+8 | | t+6=8 | | -5-7v=-61 | | 4=b-7 | | -1=b+7 | | 5+d=-7 | | k/-7=-6 | | -9+w=-12 | | 1y-5x=12 |